Intracellular Cholesterol Synthesis and Transport - Shi, Qingyang; Chen, Jiahuan; Zou, Xiaodong; Tang, Xiaochun (Frontiers in Cell and Developmental Biology, 2022)
Cholesterol homeostasis is related to multiple diseases in humans, including cardiovascular disease, cancer, and neurodegenerative and hepatic diseases. The cholesterol levels in cells are balanced dynamically by uptake, biosynthesis, transport, distribution, esterification and export. In this review, we focus on de novo cholesterol synthesis, cholesterol synthesis regulation and intracellular cholesterol trafficking. In addition, the progression of cholesterol transport between the ER and mitochondria is considered.